Knowledge and awareness of cervical cancer, its prevention and attitude towards human papillomavirus vaccine among medical students - B., Jenitha; M., Subbiah; S., Revwathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical cancer is still one of the most common cancers affecting females in India, leading to a lot of mortality and morbidity. The objective of this study was to assess the awareness of the human papillomavirus (HPV) infections and vaccination among the medical students of a tertiary care teaching hospital. Methods: A total 300 final year I and II medical students were requested to complete a questionnaire regarding cervical cancer, primary and secondary preventive measures and attitude of students towards HPV vaccination and the answers were then analysed. Results: Among 300 medical students, 46.6% were males and 53.4% were females. Most of them were aware of the common risk factors like early marriage (92.7%), multiple partners (99%), multiparity (83.3%) and HPV exposure (85.7%). Most were aware of the cervical cancer symptoms like offensive vaginal discharge (70%), irregular vaginal bleeding (92.7%) and postcoital bleeding (80.3%). 90% were aware that cervical cancer is preventable and 74% were aware that vaccine is available in India. 70% were aware about the best age to vaccinate is 9-13 years. About 10% were already vaccinated and all were females. Out of 270 students who have not administered HPV vaccine, 53.4% didn’t take the vaccine because of lack of awareness. High cost (18.8%), fear of side effects (13.8%) and doubt on efficacy (14%) were the other reasons reported for non-administration of vaccines. Conclusions: The study showed that there were gaps in knowledge regarding HPV infection and vaccination existed amongst the medical students. So, awareness among the students should be created and a more integrated teaching regarding various aspects of HPV infection, cervical cancers and its prevention needs to be introduced in the medical education system.